(untitled) (Global Journal of Medical Research, 2020)
Uterus didelphys is one of the rarest of the Mullerian duct anomalies and can lead to unique obstetric and gynecologic outcomes and considerations. This case describes a patient with known uterus didelphys and intact longitudinal vaginal septum who desired termination of pregnancy at 17 weeks gestation due to fetal anomaly. She underwent dilation and evacuation (D&E) under ultrasound guidance and the pregnancy was removed from the right-sided uterus. Preoperative mifepristone and misoprostol were used for cervical ripening. This case demonstrates that second trimester D&E can be safely performed on patients with uterus didelphys and is aided by the adjunctive use of prostaglandins, mifepristone, and ultrasound guidance to avoid intraoperative complications.